Scarlet [compact disc] - Doja Cat, 1995- (RCA Records, 2023)
Doja Cat's fourth studio album introduces a new era for the Grammy Award-winning global superstar that represents a rebirth in her career sonically and creatively. Scarlet shows the artist's versatility as a rapper, being completely written by Doja Cat throughout. The 15-track collection includes the worldwide hit Paint the Town Red.